NOVEL HYDROGENASES PURIFIED FROM THERMOCOCCUS SPP., AND METHODS FOR PRODUCING HYDROGEN USING THEREOF - LEE, JUNG HYUN; KANG, SUNG GYUN; LIM, JAE KYU; CHO, YO NA; BAE, SEUNG SEOB; JEON, JEONG HO; CHA, SUN SHIN; JEONG, IN SOON; LEE, HYUN SOOK; KIM, SANG JIN; KWON, KAE KYOUNG; KIM, YUN JAE (2016)
수소화효소(hydrogenase), 이를 암호화하는 유전자 및 이들을 이용하여 수소를 생산하는 방법에 관한 것이다. 본 발명의 수소생산방법에 따르면 상기 균주를 특정 배양조건으로 배양하는 것만으로 많은 양의 수소를 생산할 수 있으므로, 기존의 수소생산방법에 비하여 경제적이고 효율적이며, 고온에서도 수소를 생산할 수 있는 장점이 있다. The present invention relates to novel hydrogenases isolated from novel hyperthermophilic strains belonging to Thermococcus spp., genes encoding the hydrogenases, and methods of producing hydrogen using strains having the genes. According to the hydrogen production methods of the invention, a large amount of hydrogen can be produced merely by culturing the strains in specific culture conditions. Thus, the methods of the invention have advantages in that they are more economic and efficient than existing hydrogen production methods and can produce hydrogen even at high temperature.